2023
DOI: 10.3390/polym15142999
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Free-Radical Polymerization of Vinyl Monomers in View of Digital Twins

Abstract: The first case of virtual polymerization based on the concept of digital twins (DTs) is presented. The free-radical polymerization of vinyl monomers is considered to be a chain reaction consisting of a set of elementary ones. Those three types, related to the polymerization initiation and propagation as well as to the termination of polymer chain growth, are discussed. Special sets of DTs, whose total number approaches 60, distinguish each reaction type. The calculations are carried out using a semi-empirical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 83 publications
1
9
0
Order By: Relevance
“…In this paper, it will be shown that the spin theory not only perfectly senses and responds to the slightest changes occurring in RSs, but also makes it possible to predict the results of behaviors of such media that have not yet been studied. Our consideration is based on the Digital Twins (DTs) concept [70], which allows one to play a virtual game with numerous event participants [71], providing the detection of trends characteristic of these radical events.…”
Section: What Is It the C 60 Fullerene Molecule?mentioning
confidence: 99%
See 4 more Smart Citations
“…In this paper, it will be shown that the spin theory not only perfectly senses and responds to the slightest changes occurring in RSs, but also makes it possible to predict the results of behaviors of such media that have not yet been studied. Our consideration is based on the Digital Twins (DTs) concept [70], which allows one to play a virtual game with numerous event participants [71], providing the detection of trends characteristic of these radical events.…”
Section: What Is It the C 60 Fullerene Molecule?mentioning
confidence: 99%
“…Sci. 2024, 25, x FOR PEER REVIEW 3 of 23 merous event participants [71], providing the detection of trends characteristic of these radical events.…”
Section: The Root Of the C 60 Fullerene Radicalitymentioning
confidence: 99%
See 3 more Smart Citations